Local perceptions, knowledge systems and communication problems around the climate change discourse – examples from the Peruvian Andes - Weber, Anja; Schmidt, Matthias (ERDKUNDE, 2016)
This article depicts the connections between the global climate change discourse and local perceptions in the Global South using the example of village communities of the Peruvian Andes. We argue that it is necessary to understand how the global climate change discourse is transmitted, processed and adapted under specific local and socio-cultural circumstances. Our argument is based on the assumption that not only physical climate change processes influence ecosystems, economies and societies, but the discourse alone impacts livelihoods and daily routines worldwide. In this context, we discuss how the international climate change discourse is embedded in local discourses, thus defines how humans interact with existing assumptions and behaviours. Further, the discourse acts within existing global structures and runs the risk of sustaining or even reinforcing inequalities, thus excluding those who are considered to be the most vulnerable. Therefore, local knowledge must be recognised and seen as an equal aspect of (inter)national knowledge communication, creating a new balance in an equal and integrating way. This implies the need to consider national or local discourses, existing power structures and prevailing worldviews in which perceptions of time, environment, and climate are embedded. Insights from a case study in the Peruvian Andes illustrate our argumentation.